Enterprise architecture as tool for managing operational complexity in organizations (2014)
Different types of companies and organizations around the world, in spite its size, economic activity, nature, capital managed by them, and many more aspects, are heading towards diverse daily challenges that must be overcomed agilely, in order to compete successfully in a globalized world operating under highly dynamic environments. In this sense, the fact that companies in its internal operation, must be prepared well enough to respond efficiently, agile and innovative to the challenges and needs they face is taking more relevance. This paper states the importance of information technologys and the development of an enterprise architecture model, as an instrument that allows companies to face challenges related to complexity which is represented in the organization's operative environment.